UTILIZATION of SORGHUM BAGASSE MODIFIED WITH CITRIC ACID for Fe(III) ADSORPTION: KINETICS and ISOTHERM STUDIES - Bernadeta Ayu Widyaningrum; Tamara Matilda; Riska Surya Ningrum; Dwi Ajias Pramasari (Agroindustrial Technology, University of Trunojoyo Madura, 2022)
In this study, the bagasse sorghum was modified using citric acid for enhance the adsorption of Fe(III) ions. The surface morphology, surface functionality, the surface area and the pore size distribution were identified by using field emission scanning electron microscope (FESEM), Fourier transforms infrared spectroscopy (FTIR) and Brunauer and Teller (BET) and BJH method, respectively. The adsorption parameters were examined. Kinetics and isotherm were also evaluated. The kinetics models fitted well to the pseudo-second order model, indicating the adsorption mechanism of Fe(III) onto the modified bagasse sorghum (MBS) was chemisorption supported with Elovich model. For isotherm study described well by the Freundlich model (R2 = 0.941) with maximum adsorption of 45.872 mg.g-1. It was shows that the low-cost natural adsorbents MBS has potential as new promising biodegradable adsorbent for Fe(III) removal from aqueous solution